Customer satisfaction and expectation approach on regular travel package in quality service by design using fuzzy logic controller - Mohammad Nasir Saludin,; Rika Fatimah Panjaitan, (Universiti Kebangsaan Malaysia, 2004)
There are a lot of factors and conditions to be considered by tour and travel companies when designing quality product due to the fact that the product being sold is intangible and their ultimate goal is to sustain customers' loyalty. Fuzzy Logic Controller (FLC) has been observed to be compatible to this 'intangible' factor thus giving better result when compared to other methods. By using FLC, all communications are clear and have precise meaning.